An Interpretative Phenomenological Analysis ‎of Suicidal Attempts among College Students ‎in Batangas Province, Philippines - Bersoto , Myra A. (International Journal of Basic and Applied Sciences, 2025)
This qualitative study investigates the lived experiences of 13 college students in Batangas Province who have survived suicidal attempts. ‎Using Interpretative Phenomenological Analysis (IPA) and the biopsychosocial model as a framework, the research uncovered a complex ‎phenomenological landscape of suicidality. Four superordinate themes emerged from the data: The Overwhelming Nexus of Expectations, ‎driven by relentless academic pressure and profound familial obligations; Profound Disconnection and Existential Isolation, characterized by ‎a lack of peer and family support and escalating emotional numbness; The Acute Precipice of Crisis, where psychosocial stressors like rela-‎tionship dissolutions and financial strain, alongside unmanaged health comorbidities, serve as triggers; and Post-Attempt Trajectories, high-‎lighting a journey toward resilience through professional help and unexpected social support. The findings confirm that suicidality is a ‎product of converging biological, psychological, and social factors. The study proposes three culturally-tailored public health interventions—the Pamilya-Unibersidad Program (primary prevention), the Bayanihan Peer-Gatekeeper Training (secondary prevention), and the ‎Lakas Postvention Support Protocol (tertiary prevention)—to address these themes. This study’s insights and proposed tiered intervention ‎framework offer a valuable, transferable model for public health professionals to foster more resilient and compassionate communities in ‎similar sociocultural contexts‎.